Dual adoption opportunities and prospects for mining and industrial waste recovery through an integrated carbon capture, utilization and storage - Mohd Kusin, Faradiella; Syed Hasan, Sharifah Nur Munirah; M. Molahid, Verma Loretta; Soomro, Muhammad Hameer (Elsevier B.V., 2024)
Mining waste is globally available in abundance and can be seen as a useful mineral resource for long-term carbon capture which can be turned into revenue-generating products. This review highlights a new concept for mining waste utilization through an integrated carbon capture, utilization and storage (CCUS) technology in response to the long-term target for net-zero emissions. A framework for mining waste utilization by means of CCUS is introduced through integration of accelerated mineral carbonation and carbonation curing technologies. Potential CO2 sequestration of mining waste is mainly attributable to the availability of Ca-, Mg- and Fe-based silicate and oxide minerals and manipulation of process variables. It was estimated that the current rate of carbonation efficiency of mining waste through direct and indirect mineral carbonation is about 11 % and 55 %, respectively, while CO2 capture capacity through carbonation curing is about 20.6 %. It can be projected that with the current rate of CO2 sequestration, this accounts for about 21.1–100 % of the net-zero target by 2035 via CCUS. The combined mineral carbonation and carbonation curing might offset 33.4–100 % of CO2 emissions from the mining industry and 15.4–60.9 % of the net-zero target by 2050. Despite technical, economic and environmental challenges, the framework provides pathways for a sustainable mining waste recovery to meet the 2050 net-zero emissions target.